2018
DOI: 10.1155/2018/8316860
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Anti-HLA Antibodies in the First Year after Kidney Transplantation: In Whom and When Should They Be Monitored?

Abstract: The impact of the kinetics of the anti-HLA antibodies after KTx on the occurrence of acute rejection as well as the better time-point to monitor anti-HLA Abs after transplantation is not completely defined. This prospective study followed 150 patients over 12 months after transplantation. Serum IgG anti-HLA Abs were detected by single antigen beads after typing donors and recipients for loci A, B, C, DR, and DQ. Before KTx, 89 patients did not present anti-HLA Abs and 2% developed “de novo” Abs during the 1st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
2
5
0
5
Order By: Relevance
“…Finally, we found that high MFI was a risk factor for ABMR, as previously reported ( 5 , 32 34 ). However, MFI value was not correlated with the IgG3 level.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we found that high MFI was a risk factor for ABMR, as previously reported ( 5 , 32 34 ). However, MFI value was not correlated with the IgG3 level.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of IgG isotype of antibodies directed to mismatched donor human leukocyte antigen (HLA) in patients before and after kidney transplantation is considered to be a risk factor for the development of antibody‐mediated rejection (ABMR) and inferior allograft survival 1‐3 . However, not all patients with IgG donor specific antibodies (DSA) experience poor graft survival 4‐6 . In addition, ABMR may develop in the absence of IgG DSA in some cases 2,7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, not all patients with IgG donor specific antibodies (DSA) experience poor graft survival. [4][5][6] In addition, ABMR may develop in the absence of IgG DSA in some cases. 2,[7][8][9] Explanation for these phenomena may lay in the contribution of other isotypes of HLA antibodies, such as IgA, to the alloimmune response.…”
Section: Introductionmentioning
confidence: 99%
“…When patients are transplanted in the presence of DSA, frequent post-transplant monitoring is warranted. It has been shown that patients who have DSA-MFI decreased during the first two weeks after surgery, do not develop AMR, while patients with persistent or increased DSA may develop AMR if not treated in timely manner [63]. In addition, sensitized patients transplanted without preformed DSA may demonstrate rapid increase in early DSA due to B-cell memory response activation.…”
Section: Post-transplant Dsa Monitoringmentioning
confidence: 99%